Exploring the Factors Influencing Students’ Purchase Behavior for Smart Phones: An Empirical Study - Dr. Avnish Sharma, Dr. Aneesya Panicker (International Journal of Advanced Science and Technology, 2020)
There has been an enormous development in the utilization of the mobile phones in India. It is accounted for, that the India's telecommunication market is the second biggest market in the world. The mobile phones are accessible to the individuals directly from the age of 10 to 12 years. The mobile telephone innovation has brought the world closer. It gave incredible accommodation in correspondence among individuals by method for either calling or messaging. Presently, the mobile phones are used to serve many purposes like internet access, sending messages, games, access to interpersonal interaction destinations like face-book, listening music, playing the radio, and exploring books etc. Research studies say that the mobile phones are likewise used to beat the sentiment of loneliness among people. Most of the users are school and college going students belonging in the age group of 15 to 25 years. The contacts are built up in a flash with the assistance of mobile phones, which was unrealistic prior. The students are utilizing mobile phones not only for playing games, sending messages, calling while attending the class but also for serving their academic purposes as well.